State of the Science of Pretrial Release Recommendations and Supervision - Pretrial Justice Institute (My University, 2011)
Earlier this year, the Bureau of Justice Assistance (BJA) and the Pretrial Justice Institute published the document, State of the Science of Pretrial Risk ssessment.